UJI AERODINAMIK MODEL KAPAL BERSAYAP WING IN SURFACE EFFECT SEBAGAI INPUT KAJIAN GERAK PLANNING MENJELANG TAKE-OFF - Iskendar; Widodo, A. Farid; Mulyanto, Taufiq; Indiyono, Paulus (Indonesian Journal of Aerospace, 2010)
This paper describes aerodynamic tests (wind tunnel tests) for a model of Wing in Surface Effect Craft 8 seater, WiSE-8. The tests were conducted at UPT-Laboratorium Aero Gasdinamika dan Getaran (LAGG)-BPPT, PUSPIPTEK, Serpong, to determine the performance of the lift and pre-take off craft conditions. This craft model with scale of 1 per 6 was tested with rigid body - upside up - power off method. The profile of craft wing model was aerofoil form, Clark-Y. The craft model test with complete configuration (Wing-Body-Pontoon-Nacelle-Tail) was carried out with the following parameters, wind speed of 20, 30, 40, and 50 m per sec, angle of attack of -6 to 18 degree, yaw angle of 0 degree, ground board height 0-1 m (in respect to prototype value of 0-6 m). Meanwhile,the tests of air flow visualization were carried out by using wool tuft at speed of 40 m per sec. The result of wind tunnel test consisting of CL, CD, CM, and CL-CD was validated by theoritical calculation using Vortex Lattice Method (VLM) and Datcom software. Then this result was evaluated and extrapolated to predict the movement of WiSE-8 in the pre take off performance condition, especially in the longitudinal direction.